2017
DOI: 10.1016/j.nicl.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate characterization of white matter heterogeneity in autism spectrum disorder

Abstract: The complexity and heterogeneity of neuroimaging findings in individuals with autism spectrum disorder has suggested that many of the underlying alterations are subtle and involve many brain regions and networks. The ability to account for multivariate brain features and identify neuroimaging measures that can be used to characterize individual variation have thus become increasingly important for interpreting and understanding the neurobiological mechanisms of autism. In the present study, we utilize the Maha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 124 publications
(165 reference statements)
2
39
0
Order By: Relevance
“…We hypothesised that patients with a longer epilepsy duration would be associated with greater abnormalities ipsilateral to the epileptic focus. This approach has been fruitful in studies of autism and traumatic brain injury (Dean et al, 2017;Taylor et al, 2020). Applications of the Mahalanobis distance include analysing individual tracts by integrating multiple diffusion metrics into a single measure, or by pooling numerous metrics from a number of different modalities.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesised that patients with a longer epilepsy duration would be associated with greater abnormalities ipsilateral to the epileptic focus. This approach has been fruitful in studies of autism and traumatic brain injury (Dean et al, 2017;Taylor et al, 2020). Applications of the Mahalanobis distance include analysing individual tracts by integrating multiple diffusion metrics into a single measure, or by pooling numerous metrics from a number of different modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Such behavioural abnormalities are found to have certain brain-structural and physiological correlates on the level of the cortical gray matter (GM) 2 4 . It has also been found that ASD features not only GM aberrations, but also abnormal white-matter (WM) microstructure 5 7 , specifically evident as age-related difference between ASD and typical development (TD) in adolescent developmental trajectories 8 . Combining cortical features of GM and WM in one analysis might provide a more complete understanding of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Those tract-segment are then statistically tested in an univariate manner, and as such the correction for multiple comparisons -required by the typical high dimensionality of dMRI data -will hamper the discriminating power of the analysis 20 . Recently, PCA was employed to acknowledge the multivariate nature of dMRI data [20][21][22] , but this approach still relies on linear assumptions thereby ignoring possible complex interactions between the features. We believe strongly that the proposed deep autoencoder approach goes hand-in-hand with existing browser-based dMRI analysis frameworks in encouraging reproducible research and data-driven discoveries.…”
Section: Noveltymentioning
confidence: 99%
“…Second, when analyzing multiple measures (even when derived within the same tract), statistical analysis is hampered by: (i) the multiple comparisons problem; and (ii) any covariance between measurements 12,20 . Here multidimensional approaches can increase statistical power by combining the sensitivity profiles of independent modalities [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%